Model Diskursus Multi Representasi sebagai Strategi Pengembangan Kemampuan Pemecahan Masalah Matematika Siswa Sekolah Dasar - Abdul Qhadir; St Mislikhah; Abd Muhith (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2026)
Mathematical problem-solving is a core competency in elementary mathematics, yet many students still struggle to understand problems, select appropriate strategies, and evaluate solutions. Although the Discourse Multi Representation (DMR) model has been shown to improve mathematics learning outcomes, limited research has explained how it facilitates students' problem-solving processes. This study investigates the implementation of the DMR model and its role in developing mathematical problem-solving skills based on Pólya's problem-solving stages. A qualitative case study was conducted at MIN 3 Jember involving school leaders, a classroom teacher, and Grade III students. Data were collected through classroom observations, semi-structured interviews, and document analysis, then analyzed using the interactive model of Saldaña. The findings reveal that DMR enhances problem-solving by integrating three complementary elements: multiple mathematical representations, collaborative mathematical discourse, and the systematic application of Pólya's stages. Students developed stronger conceptual understanding by connecting verbal, symbolic, visual, and contextual representations while collaboratively constructing solution strategies. The effectiveness of the model was supported by teacher facilitation, productive classroom discourse, student participation, and school support. This study proposes a Conceptual Model of Discourse Multi Representation, demonstrating that mathematical problem-solving develops through the integration of representation, discourse, and structured problem-solving processes in elementary mathematics learning.